Improvements of Economic Effectiveness of the European Emission Trading Scheme: Influence of Allocation Methods - Čiegis, Remigijus; Bubnienė, Rūta (Ekonomika, 2006)
The aim of the emission trading system is to reduce emissions at the least cost to the economy and to bring environmental and economic benefits. Although the emission trading theory claims that the methodology of allocation under the conditions of a perfect market does not influence the effectiveness of the emission trading system, analysis of the Emission Trading Scheme of the European Union (EU ETS) has showed a link between the methodology chosen and its effectiveness. The article analyses the impact of the grand fathering, benchmarking and auction allocation methods on the effectiveness of the EU ETS. The article presents a comparative analysis of the national allocation plans of the EU Member States and discusses the potential demand for the allowances in the market.The implementation of the EU ETS showed that the primary and secondary market of the emissions’ allowances will be highly influenced by the allocation methods applied by the EU Member States. In theory, however, in the perfect market of allowances, the market depends on the price of the allowances only. The variety of methods applied on micro and macro levels leads to market distortions. Only a few countries have used the auctioning option to distribute the allowance, while the majority of the countries allocated the allowances for free through grand fathering and benchmarking.Due to surpluses of allowances in the EU New Member States it is likely that there will be a general surplus of allowances within the EU ETS. This precondition implies a low price of the allowances and a little liquidity of the market. The surplus of allowances and windfall profit of the electricity producers decrease the effectiveness of the system, although, following the theory of the emission trading, the price of the allowance shall be equal to the marginal emission reduction costs. In practice, the marginal costs will be lower than the price of the allowances due to the surplus of the allowances.The environmental impact of the EU ETS in the trading period 2000-07 is minor. The EU Member States, potential buyers, will use the project based on the Kyoto flexible mechanisms to meet the national greenhouse gas reduction targets. The inclusion of the external credits generated by the Joint Implementation and Clean Development Mechanisms will potentially reduce the price of the allowances in the EU ETS market.Lithuania has applied grand fathering, benchmarking and auctioning approaches in the National Allocation Plan 2000-07. The analysis concludes that Lithuanian electricity producers could become potential sellers of the allowances. During the preparation of the National Allocation Plans for 2008-12, attention should be paid to the minimisation of market distortions and harmonisation of the methodologies applied in the EU Member States. The harmonisation of the benchmarks at the EU level will promote the use of cleaner fuels and from the theoretical point of view will increase the environmental effectiveness of the EU ETS. However, such a harmonisation will not be favourable for Lithuanian enterprises that combust heavy fuel oil or orimulsion. Under harmonised benchmarks, the companies with older technologies installed would have a deficit of allowances and would have to buy the allowances or to invest in cleaner technologies. On the one hand, the harmonisation will indirectly reduce emissions of greenhouse gases, however. on the other hand this will increase the costs for the companies and subsequently the cost of electricity and heal in Lithuania. Therefore, the method should be selected taking into account and evaluating the social and economic effects to companies and the national economy.The uncertain long-term EU climate change strategy and undetermined Lithuanian long-term greenhouse gases reduction targets minimize the reliability of the investments in the sectors covered by the EU ETS. In order 10 promote the EU ETS and an active participation of the companies in the system, it is necessary to determine clearly the national strategy and allocation rules in the trading periods 2008-12 and post 2012. It is also vital to harmonise the definition of a combustion installation as well as allocation methods for new Moreover, it is important to ensure a balanced level of emission reduction in all sectors of the national economy.